Analisis Prinsip Keadilan dalam Kontrak Tanah Negara - Fatimah Fatimah; Nur Asyiah (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2025)
Purpose: This study aims to analyze the application of the principle of justice in resolving state land contract disputes based on the principle of justice in Indonesian law, as well as Indonesian land law policies that support the principle of justice in state land management contracts. Methodology: This research is a normative legal research, which examines laws and regulations, court decisions, and legal doctrines related to the principle of justice in state land contracts. The type of research used is descriptive research. It is expected that this research can provide a comprehensive understanding. Results: State land contract disputes are resolved for legal certainty in the management of state land, with the role of the government and judicial institutions based on positive law in every decision. Conclusion: Penyelesaian penyelesaian kontrak tanah negara di Indonesia harus berlandaskan prinsip keadilan distributif, korektif, prosedural, dan restoratif. Limitations: This normative study examines the causes and legal consequences of the degradation of notarial deeds and requires formal compliance, without involving empirical analysis.. Contribution: Clarifying the concept of legal policy regarding the role of the state in regulating land management in a fair and transparent manner.